Ximelagatran versus warfarin for prophylaxis of venous thromboembolism in major orthopedic surgery: systematic review of randomized controlled trials - Yoshida, Winston Bonetti [UNESP]; Dib, Regina Paolucci El [UNESP]; Yoshida, Ricardo de Alvarenga [UNESP]; Maffei, Francisco Humberto de Abreu [UNESP] (Associação Paulista de Medicina (APM), 2006)
INTRODUÇÃO: O ximelagatrano foi recentemente estudada para profilaxia do tromboembolismo venoso (TEV). OBJETIVO: Avaliar se o ximelagatrano comparado com a varfarina melhora a profilaxia do TEV em pacientes submetidos à cirurgia ortopédica do joelho. FONTE DE DADOS: Estudos randomizados identificados por pesquisa eletrônica na literatura médica, até 2006, cujos dados foram compilados no programa Review Manager, versão 4.2.5. RESULTADOS: Foram incluídos três estudos randomizados bem conduzidos envolvendo 4.914 participantes. Foram definidos dois sub-grupos com dosagens diferentes de ximelagatrano (24 mg and 36 mg, duas vezes ao dia). O tratamento com ximelagatrano mostrou freqüência significantemente menor de TEV que o tratamento com varfarina, mas somente na dosagem de 36-mg [risco relativo, RR 0.72 ([intervalo de confiança, IC, 95% 0.64, 0.81), p < 0.00001]. A freqüência de TEV no sub-grupo de 24-mg foi similar a da varfarina [RR 0.86 (IC 95% 0.73, 1.01), p = 0.06]. Para TEV maior, embolia pulmonar, sangramento e sangramento maior não houve diferença entre varfarina e a ximelagatrano. Ao final do tratamento, a elevação da alanino-aminotransferase (ALT) foi menos freqüente no sub-grupo de 24 mg de ximelagatrano que no grupo da varfarina [RR 0.33 (IC 95% 0.12, 0.91) p = 0.03], mas no período de acompanhamento essa elevação foi maior com 36 mg de ximelagatrano [RR 6.97 (IC 95% 1.26, 38.50) p = 0.03]. CONCLUSÃO: O ximelagatrano foi mais efetivo que a varfarina quando usado em dosagens maiores (36 mg, 2 vezes ao dia), mas às expensas de aumento de enzimas hepáticas no período de acompanhamento.

BACKGROUND: Ximelagatran has been recently studied for prophylaxis in surgical orthopedic cases. PURPOSE: We proposed to establish whether interventions involving ximelagatran, as compared with warfarin, would increase thromboembolic prophylaxis in patients undergoing major orthopedic knee surgery. DATA SOURCE: Studies with random assignment were identified by an electronic search of the medical literature up to 2006. Data were double-entered into the Review Manager software, version 4.2.5. DATA SYNTHESIS: We included three well-conducted clinical trials involving 4,914 participants. Sub-groups with two dosages of ximelagatran (24 mg and 36 mg, b.i.d.), were defined. Ximelagatran showed significantly lower frequency of total venous thromboembolism (VTE) than warfarin, but only with the 36-mg dosage (risk relative, RR: 0.72; 95% confidence interval, CI: 0.64-0.81; p < 0.00001). For the 24-mg subgroup, total VTE frequency was similar (RR: 0.86; 95% CI: 0.73-1.01; p = 0.06). No significant differences were shown with either ximelagatran dosage for deep vein thrombosis (DVT), pulmonary embolism, any bleeding or severe bleeding. At the end of the treatment, alanine aminotransferase (ALT) elevation was less frequent in the 24-mg ximelagatran sub-group (RR: 0.33; 95% CI: 0.12-0.91; p = 0.03], but during the follow-up period, the ALT elevation rate was greater in the 36-mg ximelagatran group (RR: 6.97; 95% CI: 1.26-38.50; p = 0.03]. CONCLUSIONS: Ximelagatran appears to be more effective than warfarin when used in higher dosages (36 mg b.i.d.), but at the expense of increased frequency of ALT elevation during the follow-up period.
Revisão sistemática de estudos comparando ximelagatrano versus varfarina para profilaxia do tromboembolismo venoso em cirurgia ortopédica
Keywords: Trombose venosa; Embolia pulmonar; Ortopedia; Prevenção primária; Metanálise; Venous thrombosis; Pulmonary embolism; Orthopedics; Primary prevention; Meta-analysis